2011
DOI: 10.1158/1940-6207.capr-10-0196
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NAG-1/GDF15 in the Inhibition of Intestinal Polyps in APC/Min Mice by Sulindac

Abstract: The antitumor effects of nonsteroidal anti-inflammatory drugs (NSAID) are assumed to be due to the inhibition of COX activity, but COX-independent mechanisms may also play an important role. NSAID-activated gene (NAG-1/GDF15) is induced by NSAIDs and has antitumorigenic activities. To determine the contribution of COX-2 inhibition and NAG-1/GDF15 expression to the prevention of colon carcinogenesis by NSAIDs, we evaluated several sulindac derivatives [des-methyl (DM)-sulindac sulfide and its prodrug DM-sulinda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…Although the precise biological functions of NAG-1 are poorly understood, it is a member of the TGF-β superfamily that exhibits pro-apoptotic and anti-tumorigenic activity in animal and cell culture models (96). A recent study by Wang and colleagues found that NAG-1 is strongly induced in the liver of Min mice after sulindac treatment suggesting that NAG-1 induction may contribute to the tumor inhibitory effects of sulindac (97). …”
Section: Molecular Targetsmentioning
confidence: 99%
“…Although the precise biological functions of NAG-1 are poorly understood, it is a member of the TGF-β superfamily that exhibits pro-apoptotic and anti-tumorigenic activity in animal and cell culture models (96). A recent study by Wang and colleagues found that NAG-1 is strongly induced in the liver of Min mice after sulindac treatment suggesting that NAG-1 induction may contribute to the tumor inhibitory effects of sulindac (97). …”
Section: Molecular Targetsmentioning
confidence: 99%
“…Evaluation by the same group of several sulindac derivatives [des-methyl (DM)-sulindac sulfide and its prodrug DM-sulindac] that do not inhibit COX-2 activity revealed that only sulindac significantly inhibited tumor formation in APC/Min mice (Wang et al, 2011). This was attributed to conversion of DM-sulindac to DM-sulindac sulfide (active form), which was less efficient than the conversion of sulindac to its active form, sulindac sulfide, in the mice.…”
Section: Evolving Role Of Nsaids In Colon Cancer Preventionmentioning
confidence: 99%
“…Sulindac inhibited polyp development in the APC/ Min mice, whereas DM-sulindac did not. Pharmacokinetic analysis showed sulindac was effectively converted to sulindac sulfide, the active metabolite, whereas DM-sulindac was rapidly excreted and not efficiently converted to the active DM-sulindac sulfide metabolite [116]. Further analysis of NAG-1 expression after sulindac treatment provided some clue as to the contribution of NAG-1 induction in sulindac-induced tumor inhibition in this study.…”
Section: Nag-1/gdf15mentioning
confidence: 79%
“…Feeding C57/BL6 mice sulindac induced mNAG-1 expression in liver and colon tissues [97, 116]. Indomethacin treatment has been shown to induce the expression of NAG-1 mRNA level in human sinonasal cancer cell AMC-HN5 xenograft tumors at a dose-dependent manner.…”
Section: Nag-1/gdf15mentioning
confidence: 99%
See 1 more Smart Citation